Exciton states of titanium dioxide nanocrystals - Pokutnii, Serhii I.; Radosz, Andrzej (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
Using a variational method within the framework of an effective mass approximation, applying a triangular coordinate system of an electron, a hole and an exciton moving in a titanium dioxide nanocrystal, an exciton energy spectrum was obtained as a function of a radius of the nanocrystal particle. It was established that the optical absorption of anatase nanocrystal, observed in the experiment, was due to the appearance of an exciton in the nanocrystal. Using a variational calculation of the energy spectrum of the exciton in the nanocrystal, a position of an absorption peak was determined.
Optica Applicata, Vol. 53, 2023, nr 4, s. 667-675
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; titanium dioxide nanocrystals; exciton state; absorption peak; mechanism of optical absorption